2022
DOI: 10.4103/njcp.njcp_630_20
|View full text |Cite
|
Sign up to set email alerts
|

Neck Muscles' Responses to Cradle, Cross-cradle and Football Breastfeeding Hold Positions in Nursing Mothers

Abstract: Background: Breastfeeding-related Neck Pain (BFNP) is prevalent in nursing mothers and cuts across the utilization of different breastfeeding (BF) hold positions. Biomechanical considerations to highlight ergonomically safe BF positions for the prevention of BFNP have not been previously studied. Aim: This study was designed to compare the electrical activities of selected neck muscles across three breastfeeding hold positions [cradle (C1), cross-cradle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is contrary to the findings of Rani et al, 12 who reported that nursing mothers in Pakistan associated the cross-cradle hold with a higher prevalence of BFRNP. In a recent study, Ojukwu et al 22 assessed the electromyographic activities of the neck muscles during different BF holds. Their findings showed that neck muscle activities were lower during the cradle hold position as compared with the cross-cradle and football holds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to the findings of Rani et al, 12 who reported that nursing mothers in Pakistan associated the cross-cradle hold with a higher prevalence of BFRNP. In a recent study, Ojukwu et al 22 assessed the electromyographic activities of the neck muscles during different BF holds. Their findings showed that neck muscle activities were lower during the cradle hold position as compared with the cross-cradle and football holds.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the mothers also reported that changing BF positions reduced their BFRNP. Previous studies 15 , 22 recommended alternating BF positions within and between BF sessions as a strategy for preventing or reducing BF-related musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 99%